Electrochemical sensor based on Pd@Nb2C nanocomposites for rapid and sensitive detection of ciprofloxacin - Haohao Zhang; Yujiao Sun; Hailing Luo; Nan Cheng; Hao Zhang (Food Science of Animal Products)
This study introduced an electrochemical sensor for the rapid, sensitive, and accurate detection of ciprofloxacin (CIP). The sensor utilized a screen-printed carbon electrode (SPCE) modified with Pd@Nb2C nanocomposites, which were prepared through the in-situ reduction of palladium nitrate on Nb2C nanosheets, resulting in a uniform distribution of Pd nanoparticles. Subsequently, they were drop-coated onto the SPCE surface, forming a Pd@Nb2C/SPCE electrochemical sensing platform. The electrochemical analysis demonstrated the excellent electrochemical performance of the sensor. Pd@Nb2C/SPCE showed a consistent linear correlation between redox peak current (IP) and CIP concentration (cCIP) in the range of 10–150 μmol/L, boasting a detection limit of 3 μmol/L. Notably, this technique tracked CIP in both whole and skimmed milk, achieving a high recoveries of 96.36%–105.40% (n = 3). Moreover, the sensor exhibited exceptional selectivity towards CIP, remaining unaffected by various interferences such as sulphonamide, amoxicillin, tetracycline, and chloramphenicol. These findings hold enormous promise for enabling real-time and rapid monitoring of CIP in milk.